Pseudonym-based privacy-preserving scheme for data collection in smart grid. (2016) - Tan, Xiaobin; Zheng, Jiangyu; Zou, Cliff; Niu, Yukun
Smart grid provides significant enhancement to the reliability and efficiency of the electricity systems, but the real-time consumption information exposes user's privacy. To tackle this challenging issue, we present a novel privacy-preserving scheme. Before smart meter (SM) joins in a network, we require Diffie-Hellman key exchange and registration to authenticate SMs. A function of the group key, time and the number of SMs is introduced to generate pseudo IDs for SMs. Then each SM sends data with its pseudo ID rather than its original ID. A simple message authentication is designed to defend against false data attack. We evaluate the privacy-preserving level by introducing an information theoretic metric - degree of anonymity. Simulations are carried out and results show that our scheme is lightweight comparing to related works.